Structural Behavior of Beam-Column Connection Using Post-Installed Steel and GFRP Rebars - Mutashar, Borkan M.; Salih, Oday Asal; Kasim , Suhaib Y. (Salehan Institute of Higher Education, 2026)
This study investigates the performance of steel and GFRP bars as post-installed reinforcement for retrofitting concrete infrastructure through experimental evaluation of the structural performance of the beam-column connection specimens. Three groups of concrete specimens were tested under flexural loading to investigate the influence of bar diameter, bar material (Steel vs. GFRP), and installation method on failure modes, load-deflection curves, and bond strength. The main failure mode at the connections was concrete breakout; however, specimens reinforced with small-diameter post-installed bars tended to fail by bar pullout. The load capacity increases by 9.64% and 12.5% when the diameter of the post-installed GFRP bar increases from 12 to 16 mm and 20 mm, respectively, and the deflection at the midspan of the beam decreases by 17.9% and 33.6% for 16 and 20 mm bars. Specimens with cast-installed reinforcements showed comparable load capacity to post-installed specimens but exhibited lower displacements. Increasing bar diameter reduced bond strength, and GFRP bars showed lower bond strength than steel bars. Overall, the results highlight the potential of GFRP bars as reliable post-installed reinforcement for strengthening critical concrete connections.